Experimental validation of a tractable numerical model for focused ultrasound heating in flow-through tissue phantoms - Huang, J; Holt, R; Cleveland, R; Roy, R (2004)
Heating from high intensity focused ultrasound (HIFU) can be used to control bleeding, both from individual blood vessels as well as from gross damage to the capillary bed. The presence of vascularity can limit one's ability to elevate the temperature owing to convective heat transport. In an effort to better understand the heating process in tissues with vascular structure we have developed a numerical simulation that couples models for ultrasound propagation, acoustic streaming, ultrasound heating and blood cooling in a Newtonian viscous medium. The 3-D simulation allows for the study of complicated biological structures and insonation geometries. We have also undertaken a series of in vitro experiments employing non-uniform flow-through tissue phantoms and designed to provide verification of the model predictions. We show that blood flow of 2 cm/s (6.4 ml/min through a 2.6 mm 'vessel') can reduce peak temperature in a vessel wall by 25%, We also show that HIFU intensities of 6.5 × 105 W/m2 can induce acoustic streaming with peak velocities up to 5 cm/s and this can reduce heating near a vessel wall by more than 10%. These results demonstrate that convective cooling is important in HIFU and can be accounted for within simulation models. © 2004 Acoustical Society of America.